Analisis Kualitas Crude Palm Oil Menggunakan Seven Tools dan Kaizen - Beni Harma; Mohammad Farid; Susriyati; Eriesta Putri Miliandini (Universitas Putra Indonesia YPTK Padang, 2022)
The main purpose of processing palm oil is to produce Crude Palm Oil (CPO) and reduce fossil fuels. In January-June 2021, the CPO produced does not meet the company's quality standards that have been agreed with consumers. Under these conditions, it is necessary to carry out production analysis activities to measure the quality of CPO, using Seven Tools method and apply the Kaizen concept. Which aims to improve the quality of CPO and improve the work system at an oil palm plantation and processing in West Sumatra. Based on the results of the analysis of CPO quality using the Seven Tools method, it is known that the low quality of CPO is caused by 3 factors, namely free fatty acid content, water content and dirt content. Where from the calculation results using the Seven Tools, the highest level that affects the low quality of CPO is the Free Fatty Acid (ALB) content which happened 20 times, followed by 15 times the dirt content and 11 times the water content in the mentioned time period. The proposal for improving the work system with the Kaizen Concept uses the 5W+1H and PDCA methods, namely, collecting fruit right after harvesting and processing oil palm fruit quickly. In order not to accumulate in a long time, the fruit sorting process is carried out carefully so that the oil palm fruit is processed according to predetermined standards, providing training based on the employee's work division so that problems do not occur, employees are encouraged to take advantage of the rest time well, so that when working can concentrate, perform inspections and maintain overall cleanliness.